Characterization of microwave and terahertz dielectric properties of single crystal La2Ti2O7 along one single direction. Issue 14 (November 2021) - Zhang, Man; Tang, Zhiyong; Zhang, Hangfeng; Smith, Graham; Jiang, Qinghui; Saunders, Theo; Yang, Bin; Yan, Haixue
Highlights: Single crystal La2Ti2O7 shows ferroelectric switching. Its MW and THz properties along one single direction were characterized. Decrease in permittivity with frequency is due to relaxation of domain walls. Abstract: New generation wireless communication systems require characterisations of dielectric permittivity and loss tangent at microwave and terahertz bands. La2 Ti2 O7 is a candidate material for microwave application. However, all the reported microwave dielectric data are average value from different directions of a single crystal, which could not reflect its anisotropic nature due to the layered crystal structure. Its dielectric properties at the microwave and terahertz bands in a single crystallographic direction have rarely been reported. In this work, a single crystal ferroelectric La2 Ti2 O7 was prepared by floating zone method and its dielectric properties were characterized from 1 kHz to 1 THz along one single direction. The decrease in dielectric permittivity with increasing frequency is related to dielectric relaxation from radio frequency to microwave then to terahertz band. The capability of characterizing anisotropic dielectric properties of a single crystal in this work opens the feasibility for its microwave and terahertz applications.